2022
DOI: 10.1002/ccr3.6425
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 hospitalization with later long COVID in a person with Down syndrome

Abstract: Viruses that induce pulmonary difficulties and auto-inflammation are more common in people with Down syndrome. They also have a higher number of comorbidities associated with a worse prognosis than the overall population.Adult patients with acute COVID-19 are increasingly being diagnosed with Long COVID. However, patients with Down syndrome with later long COVID-19 are the first example documented in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Hypothyroidism was persistent; 7 , 19 , 24 , 32 , 35 , 38 , 39 Malle et al 19 demonstrated a 50% prevalence among patients with DS hospitalized due to COVID-19. Despite this, thyroid disease did not appear to have played a direct role in the progression of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypothyroidism was persistent; 7 , 19 , 24 , 32 , 35 , 38 , 39 Malle et al 19 demonstrated a 50% prevalence among patients with DS hospitalized due to COVID-19. Despite this, thyroid disease did not appear to have played a direct role in the progression of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the coronavirus family, in general, has developed strategies to evade the effects of IFN, which probably also occurred with SARS-CoV-2. 32 , 51 , 68 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations